#### Answer

x=-8

#### Work Step by Step

Simplifying
8(x + -5) = 13x
Reorder the terms:
8(-5 + x) = 13x
(-5 * 8 + x * 8) = 13x
(-40 + 8x) = 13x
Solving
-40 + 8x = 13x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13x' to each side of the equation.
-40 + 8x + -13x = 13x + -13x
Combine like terms: 8x + -13x = -5x
-40 + -5x = 13x + -13x
Combine like terms: 13x + -13x = 0
-40 + -5x = 0
Add '40' to each side of the equation.
-40 + 40 + -5x = 0 + 40
Combine like terms: -40 + 40 = 0
0 + -5x = 0 + 40
-5x = 0 + 40
Combine like terms: 0 + 40 = 40
-5x = 40
Divide each side by '-5'.
x = -8
Simplifying
x = -8